PERTANGGUNGJAWABAN PIDANA PEKERJA SEKS KOMERSIAL DALAM TINDAK PIDANA PROSTITUSI SECARA ONLINE BERDASARKAN UNDANG UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI POLRESTA PEKANBARU - Risgaluh Maulidya; Erdianto Effendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Arrangements regarding the prohibition of online prostitution has beenformulated clearly in positive law but law enforcement in this case is very difficultto do. This is due to the difficulty of determining the jurisdiction of prostitutiononline criminal act in Indonesia, especially in Pekanbaru become a seriousproblem currently faced. Therefore online prostitution should be addressed in arational way. One rational efforts is with law enforcement policies. The purposeofthis study are to know the law enforcement against criminal acts of onlineprostitution in jurisdiction of Police Pekanbaru City resort, to know the policebarriers in law enforcement against criminal acts of online prostitution injurisdiction of Police Pekanbaru City resort, and to know the efforts made ofPolice to overcome obstacles in law enforcement against criminal acts of onlineprostitution in jurisdiction of Police Pekanbaru City resort. This type of researchis a juridical sociological research, the data sources used, the primary data,secondary data and data tertiary, data collection techniques in this study withinterviews and literature study. Law enforcement against criminal acts of onlineprostitution in jurisdiction of Police Pekanbaru City resort not running optimallybecause of the presence of obstacles, obstacles encountered in law enforcementagainst criminal acts of Phedofilia in jurisdiction of Police Pekanbaru City resortis in the form of internal factors and external factors, efforts to overcome thisbarrier is increasing the number of personnel investigator PPA and increaseknowledge of investigator in understanding the law enforcement.Keywords : Criminal Responsiblity – Online Prostitution